AYOLLAR ZAMONAVIY LIBOSLARIDA QUROQ TURLARINI QO‘LLASHNING O‘ZIGA XOS XUSUSIYATLARI - Berdimbetova, A.D. (SCIENCE and SOCIETY, 2024)
The most important feature of the use of types of triggers in women's clothing is that women's clothing is nationalized. Because today, in the process of globalization of the peoples of the world, the preservation of national values, traditions and customs and their further development is one of the important issues.
Keywords: fashion and design; clothing; beautiful; aesthetic; application nationality; fabric; tailoring; fantasy; satin fabric; modern; women